Time's melody - Murdoch, Tessa (Apollo (London. 1925), 2013)
Musical clocks designed by Charles Clay and fellow 18th-century clockmakers harnessed the success of Italian opera to rank among the popular entertainments of Georgian London; this winter, they are the subject of a special exhibition at London's Handel House Museum In 2009 the Victoria and Albert Museum in London acquired a gilt-bronze relief representing Apollo with Time and Harmony (Fig. 2).1 The figures were modelled by the sculptor Michael Rysbrack (1694-1770); the background was painted in oil on copper with simulated architecture framing the nine muses by Jacopo Amigoni (c. 1685-1752), a Venetian painter who came to London from Munich in 1729 and decorated the new Covent Garden Theatre in 1732.2 The gilt-bronze relief had been identified as the front plate of a musical clock, as the aperture filled with drapery was originally intended for a dial. London was also celebrated for horology; clock and watchmaking were firmly established in the English metropolis by 1700 and serviced a wide-ranging export trade. [...]English clockmakers settled in the major European cities in order to meet the increased demand for fashionable time-pieces. The same clock featured again a week later at Fawkes's Theatrical Booth at the Southwark Fair in September 1735.17 Tickets for the Italian Opera could be purchased at Mrs Chenevix's 'toy shop', a fashionable venue established by her husband in 1731 which sold expensive adult accessories including watches and snuffboxes, in Suffolk Street, adjacent to Haymarket and close to the King's Theatre; her brother William Deards also sold opera tickets at his toy shop opposite St Dunstan's Church in Fleet Street.18 The idea of marketing commemorative luxury goods for the new generation of opera lovers was probably developed by such shopkeepers who provided fashionable society with the opportunity to handle the latest inventions and designs in horology and goldsmiths' work. Perhaps that example will inspire a Chinese and Italian Maecenas to fund the restoration of the musical clocks by Clay in Beijing and Naples. ^ Acknowledgements With thanks to Sarah Bard we 11, Jonathan Betts at the Royal Observatory,Greenwich, Rufus Bird, Deputy Surveyor of the Royal Collection; Vanessa Brett, Brittany Cox, Martin Ellis at Birmingham Museum and Art Gallery, Richard Higgins, Luisa Mengoni at the V&A, Anna Lisa Porzioat the Royal Palace, Naples, Roger Smith, Anthony'Rimer, Martin Wyatt and Zan Yhangat the Palace Museum, Beijing and the staff of theSpeelklok Museum, Utrecht. 1/ Victor iaand Albert museum number M.29-2009.